Incidencias de las enfermedades de la población de 0 - 12 años en Parroquia Iberia, en relación a contaminación del Río Jubones - Zeas Ramírez, Diana J. (2006)
In this carried out study you to proven the existences of a great one numbers of infect-contagious illnesses that have affected the infantile population understood among 0-12 in the sector The Iberia canton El Guabo. With direct relationship to the consumption of the water of the one laughed jerkins, having basic cause the half environmental contamination that affects us at the present time.